Zopalki - Circle (yhtye : 1991-); Ahtiainen, J.; Elo, T.; Hagner, Petri; Hietaniemi, Jukka-Pekka; Lehtisalo, J.; Päivistö, M.; Bad Vugum (Bad vugum, 1996)
13 kappaletta.
Circle (yhtye): J. Ahtiainen, J.-P. Hietaniemi, T. Elo, J. Lehtisalo, P. Hagner, M. Päivistö.
Äänitys: 1995-1996, Laserstudio.
PUUTELUETT.
Puuttuu kansalliskokoelmasta
[Äänite].
Keywords: Circle (yhtye : 1991-) -- albumit; psykedeelinen rock